Akses dan Ekslusi dalam Reformasi Hutan di Sumatera: Studi Kasus di Nagari Simanau, Kecamatan Tigo Lurah, Kabupaten Solok, Sumatera Barat - Maskota Delfi; Yetty Oktayanty (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
This article discusses the village forest in Simanau. This research was conducted by using a qualitative method, one of which is a case study. Data collection was carried out by observation, interviews and literature study. Research departs from solutions to the problem of deforestation and forest degradation as business as usual or with international assistance through the village forest scheme. Village forests are one of Nawacita's priority programs as a strategic step in reducing deforestation and forest degradation and also overcoming poverty and poverty in national land tenure. My intension is to analyze the forest from a critical anthropological perspective, one of which is the political ecology framework to explore the village forest in Simanau. For this reason, I use the concepts of "access" and "exclusion" in sharpening economic goals in ecological terms. The research findings show that Simanau forest reform raises a dilemma where access to forests is limited for non-management communities. The concept of access is used to hide who gets (and doesn't get) the benefits of the existence of the village forest and through what they get it. This concept of access is then related to the concept of exclusion which means preventing people from accessing forests.